UNDERGROUND ECONOMY DALAM SEBUAH PERSPEKTIF - Kristianto, Aloysius Hari; Dedy; Fentura, Bona (Business, Economics dan Entrepreneurship, 2020)
This article aims to describe the activities of underground economic actors. This article is a literature review of several empirical studies in Indonesia and the world in examining or resolving the impact of the existence of these economic activities. There are several terms used in each country from the underground economy, such as black economy, shadow economy and unofficial economy. Every country, both developed and developing countries, have experienced underground economic activity that continues to increase so that biased measurement often occurs, which is caused by indicators of underground economy that cannot be measured clearly and this economic activity can harm state revenues. The driving force of the underground economy is an increase in the tax burden (directly or indirectly), combined with labor market regulations and the quality of public goods and services, as well as properly measured economic conditions. The need for systematic oversight to reduce the number of corruption by providing convenience to the community through the E-Government program as a direction for the creation of Good Governance..